2022
DOI: 10.1039/d2ra00232a
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymersviareversible addition–fragmentation chain-transfer synthesis in sensing and environmental applications

Abstract: Environmental contaminants constitute an ecological and health hazard, which requires green sensing. The RAFT-MIP approach for tailor-made selective receptors enhances them via binding affinities for use in environmental contaminant sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 152 publications
0
27
0
Order By: Relevance
“…These techniques were influenced by the type of interactions observed between the functional monomer and the template molecules or target analytes [27]. Interestingly, Mosbach and coworkers focused their research on employing the non-covalent technique for polymer-based imprinting, while Wulff and his research group used the covalent approach in creating the imprints [30]. The main difference between these two techniques is related to the removal or detachment of the template molecules from the polymer framework [27,30].…”
Section: History Of Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%
See 2 more Smart Citations
“…These techniques were influenced by the type of interactions observed between the functional monomer and the template molecules or target analytes [27]. Interestingly, Mosbach and coworkers focused their research on employing the non-covalent technique for polymer-based imprinting, while Wulff and his research group used the covalent approach in creating the imprints [30]. The main difference between these two techniques is related to the removal or detachment of the template molecules from the polymer framework [27,30].…”
Section: History Of Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%
“…Interestingly, Mosbach and coworkers focused their research on employing the non-covalent technique for polymer-based imprinting, while Wulff and his research group used the covalent approach in creating the imprints [30]. The main difference between these two techniques is related to the removal or detachment of the template molecules from the polymer framework [27,30]. The template removal plays an integral part of the binding affinity for targets, hence it was confirmed that the covalent technique produced more uniformly distributed binding sites while the non-covalent technique yielded non-homogenous binding sites [27].…”
Section: History Of Molecularly Imprinted Polymers (Mips)mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other living/control radical polymerization techniques, RAFT polymerization not only allowed the synthetic tailoring of polymers with narrow molecular weight distribution, controlled molecular weight, and diverse terminal functionality, but has also been performed under mild reaction conditions with a wide range of monomers. Therefore, the specially-designed polymer structure can been used to improve the features of molecular imprinting such as maximum adsorption capacity, selectivity, and sensitivity [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Important parameters such as solvent polarity, reaction temperature, and stirring speed significantly influence the size and morphology of MIPs particles in this method [ 9 ]. RAFT is a slow, thermodynamically controlled technique that allows polymer chain growth and produces homogeneous polymers [ 10 ]. In the sol–gel method, solid nanoparticles dispersed in a liquid (a sol) aggregate together to form a continuous three-dimensional network that extends throughout the liquid (gel).…”
Section: Introductionmentioning
confidence: 99%